(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
India is an agricultural nation with good land availability for agricultural activities, and a sizable population is still engaged in agriculture and enterprises that are related to it. Agripreneurship may boost the economy, increase revenue, and open many business opportunities in rural regions. Effective agricultural entrepreneurship efforts may also help the agripreneurs who are dealing with long term economic issues including urbanization, poverty, and unemployment. They deal with issues like financial difficulties in supporting farmers, promoting agricultural products, transportation, women’s emancipation, tribal youth development, and a few others. These issues include income diversification, growth, increased employment, new technology, and the best possible use of the available resources.The main issue with liberalization, privatization and globalization is that the entire region has become like a neighbouring market in which our farmers and commodities will have to compete with foreign companies in terms of quality and price. The Indian economy is primarily agrarian. Agriculture directly employs around 65 percent of the Indian people and accounts for 16-17 percent of India’s GDP. The present survey is being conducted in the Ongole area of the Prakasam district, Andhra Pradesh. The paper is aimed at problems &prospects of agriprenures. The questionnaire is prepared with 21 relevant questions to collect primary data. Respondents were asked to respond on five points lickered scale. The questionnaire is given to 128 people among agriprenures and 105 are returned and 90 responded properly. To analyses, the primary M.S excel has been used. Channel of distribution & Financial support is as significantly affecting the agrepreneurs.